Effect of Peptides on New Taste Sensation: Kokumi-Review - Feng, Tao; Zhang, Zhiwen; Zhuang, Haining; Zhou, Jinjie; Xu, Zhimin (Mini-Reviews in Organic Chemistry, 2016)
With the improvement of living standards and dietary habits, the flavor and quality of food are highly sought after; therefore people are pursuing to experi- ence more delicious food. Many researchers in food flavor area are seeking mole- cules which make food more delicious and healthier. More and more investigators are studying the relation between taste molecules and gustation receptor. Kokumi taste is a kind of sensory feeling, such as thickness, mouthfulness, complexity, and increasing the continuity of the perception of food taste at the same time. As a new defined taste, in the sensory area, kokumi taste is being studied. This article deals with the finding of kokumi taste, detection of kokumi substances, and discussing kokumi taste mechanism. The major section of this review will relate to the kokumi- tasting components which have been published lately, such as y-glutamyl peptides etc.
Keywords: taste